Genomic characterization of two Xanthomonas phaseoli pv. phaseoli strains of Italian origin reveals novel TAL effectors and putative susceptibility gene targets - A. Gaiti; G. M. Balestra; N. S. Iacobellis; E. Avite; C. M. Pozzi; D. Bulgari; M. Saracchi; A. Kunova; P. Cortesi; M. Pasquali (Journal of Plant Pathology, 2026)

KPC-producing Klebsiella pneumoniae in Switzerland from 2024 to 2025: comparative genomics and cefiderocol resistance mechanisms analyses - Jacqueline Findlay; Patrice Nordmann; R Lienhard; L Vonallmen; C Schilt; A Scherler; K Lucke; M Jutzi; M Reichmuth; U Schibli; C Fricker; S Pranghofer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Multi-detector neutron noise analysis of a reflected Pu Sphere - Juliann R. Lamproe; Flynn B. Darby; Jesson D. Hutchinson; Theresa E. Cutler; Shaun D. Clarke; Sara A. Pozzi (Annals of Nuclear Energy, 2026)

In vitro activity of β-lactamase inhibitors avibactam, relebactam and vaborbactam in combination with aztreonam against metallo-β-lactamase producing Escherichia coli clinical isolates - Clément Viguier; Samanta Freire; Maxime Bouvier; Christophe Le Terrier; Laurent Poirel; A. Westers; M. Imperiali; L. Pozzi; D. Balzari; G. Vaninetti; C. Cirillo; V. Gaia; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Fishing out microorganisms for bioremediation using metagenomics: Isolation and whole-genome sequencing of the metabolically versatile Rhodococcus erythropolis LP27217 strain from oil spill lake - Emilio D’Ugo; Arghya Mukherjee; Marco Resitano; Roberto Giuseppetti; Daniela Fortini; Bruna Matturro; Mattea Chirico; Maria Elena Pisanu; Matteo Tucci; Roberta Pozzi; Nicola Lovecchio; Owczarek Slawomir; et al. (Journal of Hazardous Materials, 2025)

Combined resistance mechanisms leading to high-level of cefiderocol resistance among NDM-like producing E. coli ST167 clinical isolates - Mustafa Sadek; Juan Bosch Duran; Trinad Chakraborty; Laurent Poirel; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; V. Slutter; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Summary Purpose A series of NDM-producing Escherichia coli ST167 clinical isolates exhibiting resistance to cefiderocol (FDC), with no previous exposure to this antibiotic, were analyzed in this study. Methods The antimicrobial susceptibility testing and phenotypic detection of resistance patterns (Rapid Cefiderocol NP test and MIC determination) were performed for all tested isolates. Their entire genomes were sequenced by using the Illumina MiSeq platform and high-quality reads were de-novo assembled using the CLC Genomic Workbench. Genome-sequence based characteristics were analyzed using bioinformatics tools. Results All NDM-producing E. coli ST167 isolates showed a high level of resistance to FDC (MICs being 64 or > 64 mg/L). The chromosomally located cirA gene, encoding a catecholate siderophore receptor in E. coli , was truncated in all FDC-resistant isolates due to a frameshift mutation (S90Y), leading to CirA-deficient isolates. A four amino acid insertion (YRIN) was also identified after residue 333 in the PBP3 protein sequence of all E. coli isolates. Among them, a single FDC-resistant NDM-5-producing E. coli isolate (1006) was additionally resistant to aztreonam/avibactam (AZA MIC of 8 mg/L). When analyzed against the genome of another FDC resistant NDM-5 producing E. coli ST167 containing a YRIN insertion in the PBP3, and exhibiting decreased susceptibility to AZA, the broad-spectrum ß-lactamase CMY-42 was identified. Conclusion We identified a variety of NDM-producing E. coli isolates exhibiting high level of resistance to FDC as a result of the combined effect of CirA deficiency, along with production of NDM-type enzymes. The spread of such resistance phenotype across Europe poses great concern on the clinical efficacy of this novel drug. Additionally, the identification of an FDC- and AZA-resistant NDM-5 producing E. coli isolate represents one of the ultimate evolutions with a possible step towards pan-resistance.

Freeze or escape? Tadpoles' behavioural decisions based on conspecifics' chemical alarm cues - Lucas D. Jungblut; Araceli R. Coceres; Marilina Raices; Carola A.M. Yovanovich; Andrea G. Pozzi (Animal Behaviour, 2025)

Intelligent Radiation: A review of Machine learning applications in nuclear and radiological sciences - Abbas J. Jinia; Shaun D. Clarke; Jean M. Moran; Sara A. Pozzi (Annals of Nuclear Energy, 2024)

Molecular analysis of metallo-beta-lactamase-producing Pseudomonas aeruginosa in Switzerland 2022–2023 - Jacqueline Findlay; Otavio Hallal Ferreira Raro; Laurent Poirel; Patrice Nordmann; R. Lienhard; L. Vonallmen; C. Schilt; A. Scherler; K. Lucke; M. Jutzi; M. Reichmuth; U. Schibli; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Objectives The occurrence of metallo-beta-lactamase-producing Pseudomonas aeruginosa (MBL-PA) isolates is increasing globally, including in Switzerland. The aim of this study was to characterise, phenotypically and genotypically, the MBL-PA isolates submitted to the Swiss National Reference Center for Emerging Antibiotic Resistance (NARA) reference laboratory over a 12-month period from July 2022 to July 2023. Methods Thirty-nine non-duplicate MBL-PA Isolates were submitted to NARA over the study period from across Switzerland. Susceptibility was determined by broth microdilution according to EUCAST methodology. Whole-genome sequencing was performed on 34 isolates. Sequence types (STs) and resistance genes were ascertained using the Centre for Genomic Epidemiology platform. MBL genes, bla NDM-1 , bla IMP-1 , and bla VIM-2 , were cloned into vector pUCP24 and transformed into P. aeruginosa PA14. Results The most prevalent MBL types identified in this study were VIM (21/39; 53.8%) followed by NDM (11/39; 28.2%), IMP (6/39; 15.4%), and a single isolate produced both VIM and NDM enzymes. WGS identified 13 different STs types among the 39 isolates. They all exhibited resistance to cephalosporins, carbapenems, and the beta-lactam-beta-lactamase inhibitor combinations, ceftolozane-tazobactam, ceftazidime-avibactam, imipenem-relebactam, and meropenem-vaborbactam, and 8 isolates were cefiderocol (FDC) resistant. Recombinant P. aeruginosa strains producing bla NDM-1 , bla IMP-1 , and bla VIM-2 exhibited FDC MICs of 16, 8, and 1 mg/L, respectively. Conclusions This study showed that the MBL-PA in Switzerland could be attributed to the wide dissemination of high-risk clones that accounted for most isolates in this study. Although FDC resistance was only found in 8 isolates, MBL carriage was shown to be a major contributor to this phenotype.

Preliminary verification of the MCNP perturbation and fixed-source tally sensitivity tools - Juliann R. Lamproe; Theresa E. Cutler; Michael Y. Hua; Jesson D. Hutchinson; Michael E. Rising; Shaun D. Clarke; Sara A. Pozzi (Annals of Nuclear Energy, 2023)

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

Laboratory simulation of fault reactivation by fluid injection and implications for induced seismicity at the BedrettoLab, Swiss Alps - G. Volpe; G. Pozzi; C. Collettini; E. Spagnuolo; P. Achtziger-Zupančič; A. Zappone; L. Aldega; M.A. Meier; D. Giardini; M. Cocco (Tectonophysics, 2023)

REST-Dependent Presynaptic Homeostasis Induced by Chronic Neuronal Hyperactivity - F. Pecoraro-Bisogni; Gabriele Lignani; A. Contestabile; E. Castroflorio; D. Pozzi; A. Rocchi; C. Prestigio; M. Orlando; P. Valente; M. Massacesi; F. Benfenati; Pietro Baldelli (Molecular Neurobiology, 2018)

Mitogen-activated protein kinases are involved in hepatocanalicular dysfunction and cholestasis induced by oxidative stress - Flavia D. Toledo; Cecilia L. Basiglio; Ismael R. Barosso; Andrea C. Boaglio; Andrés E. Zucchetti; Enrique J. Sánchez Pozzi; Marcelo G. Roma (Archives of Toxicology, 2017)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The Ca2+-calmodulin-Ca2+/calmodulin-dependent protein kinase II signaling pathway is involved in oxidative stress-induced mitochondrial permeability transition and apoptosis in isolated rat hepatocytes - Flavia D. Toledo; Leonardo M. Pérez; Cecilia L. Basiglio; Justina E. Ochoa; Enrique J. Sanchez Pozzi; Marcelo G. Roma (Archives of Toxicology, 2014)

Physiological concentrations of unconjugated bilirubin prevent oxidative stress-induced hepatocanalicular dysfunction and cholestasis - Cecilia L. Basiglio; Flavia D. Toledo; Andrea C. Boaglio; Sandra M. Arriaga; Justina E. Ochoa; Enrique J. Sánchez Pozzi; Aldo D. Mottino; Marcelo G. Roma (Archives of Toxicology, 2014)

Use of EPR and FTIR to detect biological effects of ultrasound and microbubbles on a fibroblast cell line - D. Pozzi; P. Fattibene; D. Viscomi; L. Di Giambattista; P. Grimaldi; I. Udroiu; A. Bedini; C. Giliberti; R. Palomba; A. Congiu Castellano (European Biophysics Journal, 2011)

UVB radiation induced effects on cells studied by FTIR spectroscopy - Lucia Di Giambattista; P. Grimaldi; S. Gaudenzi; D. Pozzi; M. Grandi; S. Morrone; I. Silvestri; A. Congiu Castellano (European Biophysics Journal, 2010)

COSII genetic maps of two diploid Nicotiana species provide a detailed picture of synteny with tomato and insights into chromosome evolution in tetraploid N. tabacum - Feinan Wu; Nancy T. Eannetta; Yimin Xu; Jörg Plieske; Martin Ganal; Carlo Pozzi; Nicolas Bakaher; Steven D. Tanksley (Theoretical and Applied Genetics, 2010)

Amphibian larvae and zinc sulphate: a suitable model to study the role of brain-derived neurotrophic factor (BDNF) in the neuronal turnover of the olfactory epithelium - Carola A. M. Yovanovich; Lucas D. Jungblut; Tamara Heer; Andrea G. Pozzi; Dante A. Paz (Cell and Tissue Research, 2009)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)